Pandemic, Memory, and Narrative Imagination: Reconfiguring Crisis in Contemporary Literary Discourse - Razavi , Bentul Huda (SMART MOVES JOURNAL IJELLH, 2023)
The COVID-19 pandemic has prompted a significant reorientation in literary expression, compelling writers to engage with crisis not only as an event but as an ongoing condition that reshapes perception, memory, and social relations. This paper examines pandemic literature as a dynamic narrative field that extends beyond documentation into critical interpretation. Situating contemporary texts within a longer literary tradition, the study explores how themes such as isolation, vulnerability, ethical responsibility, and resilience are rearticulated in post-2020 writing. Through an analysis of selected works across memoir and fiction, the paper argues that pandemic narratives increasingly foreground interiority, fragmentation, and lived experience over grand historical abstraction. These texts resist closure and certainty, instead inhabiting ambiguity as a central mode of meaning-making. By engaging with the uneven realities of crisis and exposing underlying socio-political inequalities, contemporary pandemic literature redefines the relationship between narrative and lived experience. The paper suggests that such writing functions as a cultural archive as well as a site of imaginative reconstruction, where crisis is not only recorded but critically reframed.